PENGENALAN KENDALI ROBOT SAMPAH BERBASIS IPAD DI SMPIT HARAPAN MULIA PALEMBANG - Nyayu Latifah; Ade Silvia Handayani; Yudi Wijanarko; Ekawati Prihatini; Selamat Muslimin; Yeni Irdayanti; Destra Andika Pratama (Politeknik Negeri Sriwijaya, 2020)
SMPIT Harapan Mulia is one of the schools that uses iPad for its teaching and learning activities. The use of this small, simple and lightweight iPad is certainly one of the solutions to reduce the burden of the books that the students should carry. All the learning materials can be found easily in the iPad, therefore the students can learn many things anywhere and anytime. In addition, the use of this iPad also will certainly make the students to more focus on the lesson. The students have an opportunity to be more flexible in terms of self-development. Besides the benefits provided by the iPad, there are several obstacles that are often faced, including, the use of iPad is monotonous andexcessive use of iPad can reduce student performance compared to those who do not use tablets (according to research from the Organization for Economic Cooperation and Development (OECD) and University of Michigan). Based on observations and interviews with the principal at SMPIT Harapan Mulia, students who use the iPad are more enthusiastic in joining the teaching and learning process. This can be proven by an increase in the average value obtained by the students of SMPIT Mulia Harapan. However, unfortunately the school also often found the students looked bored with their tablets. This is because their iPad is connected directly to MDM (Mobile Device Management), where the MDM manages the content and activities on each student's iPad. This MDM limits the student's movement, so that they will not get out of line. However, this MDM also makes students feel uncomfortable and not to be free to express themselves. Therefore, we need a solution to overcome these problems. This dedication is carried out with the aim to maintain the stability of the students' enthusiasm in using the iPad. In practice, this service provides opportunities for students to develop their skills in using the iPad. Students are equipped with the theory of the development of the use of iPad (in this activity, the iPad is used to control the trash robot). Besides that, the service activity also demonstrated and gave a short workshop on the control of garbage robots using the iPad. The results of this dedication were a simple coding and a monitoring module using a Blynk based iPad.